STUDY ON SOLID WASTE COLLECTION AND DISPOSAL IN HOSPITALS AND HEALTA CARE CENTERS OF TEHRAN PROVINCE - A. Omrani; K. Imandel; H. Karimzadegan (Tehran University of Medical Sciences, 1998)
The main objective of this investigation was to achieve a clear pattern of solid waste collection and disposal in selected hospital and health care establishments in certain cities of Tehran province. This study was done in more than 82 percent of all hospitals with 3017 beds during the year 1996. Solid waste produced per bed was evaluated to be 2.87 kg per day which was 8670 kg per day, for all beds, comprising less than 1% of the total solid waste generated in the same cities during the same period. According to the information gathered in the 84.2% hospitals and health care centres, solid wastes were collected manually by labourers from various sections. Detention time of the waste in 89.5% of the cases was nearly 24 h. Densities of this type of waste were estimated to be 193.18kg/m3 with plastic bag and 247.72 kg/m3 without bag. Physical analysis of the wastes indicated 15.1% plastic and rubbery, 9.6% linen, 12.45% paper and cardboard, 8.5% various types of metals, 1.7% glass and 52.4% other different materials. In Iran, hospital administrations are directly responsible for collection transport and ultimate disposal of hospital wastes. Incinerators installed in 21.1% of the clinical centres, were not operating at all. Overall conclusion is that, solid wastes collection transportation and disposal in Tehran district is not satisfactory, according to the health and management criteria.